ԺԵ. դարում ստեղծագործած Մանուել մանրանկարչի ՄՄ Հմր 5784 ձեռագիրը - Սիրանուշ Բեգլարյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье представлена первая иллюстрированная рукопись миниатюриста 15го века Мануела. В ней дано описание миниатюр позднего периода, и по общей схеме определен их иконографический тип. Делается также сравнительный анализ миниатюр Мануела с сюжетными миниатюрами двух других рукописей. На основе общей иконографической схемы выявлена школа художника. The article represents the first illuminated manuscript of the miniaturist Manuel, the 15th century. It gives an account of the late period miniatures and the definition of their iconographic type by a general scheme. A comparative analysis of Manuel’s illuminations with the narrative cycles of two other manuscripts is also presented. On the basis of the general iconographic scheme an attempt is made to reveal the illuminator’s school.
Keywords: Bibliography; Biography; Auxiliary Sciences of History; Manuscripts; Paleography; Fine Arts; Illuminating of Manuscripts and Books